Inhibiting and Supporting Factors that Influence Caregiver Performance - Aristyanto, Moh. Fahri Wahyu; Nawawi, Juanda; Arifin, Indar (Journal of Management and Administration Provision, 2025)
The Institute of Public Administration (IPDN) is a civil service educational institution that aims to form cadres of state civil servants with integrity, discipline, and professionalism. As a long-term government effort to support bureaucratic reform, IPDN provides free education to selected cadets, who after graduating are immediately appointed as civil servants. This study aims to evaluate the performance of caregivers, especially Kasat Dharma, in forming the personality of cadets at IPDN South Sulawesi Campus. This study uses a descriptive qualitative approach, with data collection methods through semi-structured interviews, observation, and documentation. Informants were determined through purposive sampling techniques that included caregivers, cadets, and campus structural officials. The results of the study showed that the performance of Kasat Dharma was quite good in terms of coaching, although there were still obstacles in interpersonal communication and coordination between units. Based on Herzberg's two-factor theory, it was found that supporting factors for Kasat Dharma's performance include intrinsic motivation such as moral responsibility, pride in the results of coaching, and high dedication. Meanwhile, inhibiting factors include the limited number of caregivers, minimal training, lack of supporting facilities, and a less than optimal coordination system. The combination of these two factors affects the stability and effectiveness of the overall performance of caregivers. Therefore, improving the work environment and strengthening the support system needs to be done in order to maintain and improve the performance of caregivers in a sustainable manner.